Single Cell Analysis Identifies the miRNA Expression Profile of a Subpopulation of Muscle Precursor Cells Unique to Humans With Type 2 Diabetes - Henriksen, Tora I.; Heywood, Sarah E.; Hansen, Ninna S.; Pedersen, Bente K.; Scheele, Camilla C.; Nielsen, Søren (Frontiers in Physiology, 2018)
MicroRNAs (miRNAs) take part in regulating central cellular processes such as differentiation and metabolism. We have previously shown that muscle progenitor cells derived from individuals with type 2 diabetes (T2DM) have a dysregulated miRNA profile. We hypothesized that the T2DM muscle progenitor population is heterogeneous in its miRNA expression and differs from the progenitor population of healthy controls. MiRNA expression profiles of CD56+ muscle progenitor cells from people with T2DM and from healthy controls were therefore investigated at a single cell level. Single-cell analysis revealed three subpopulations expressing distinct miRNA profiles: two subpopulations including both T2DM and healthy control muscle precursors presented miRNA expression profiles mostly overlapping between groups. A distinct third subpopulation consisted solely of cells from donors with T2DM and showed enriched expression of miRNAs previously shown to be associated with type 2 diabetes. Among the enriched miRNAs was miR-29, a regulator of GLUT4 mRNA expression. Interestingly, this subpopulation also revealed several miRNAs with predicted targets in the PI3K/ Akt pathway, not previously described in relation to T2DM muscle dysfunction. We conclude that a subpopulation of T2DM muscle precursor cells is severely dysregulated in terms of their miRNA expression, and accumulation of this population might thus contribute to the dysfunctional muscular phenotype in type 2 diabetes.